Unveiling the Core Design Elements of Bamboo Furniture - Wei Liu; Yi-Nan Fei; Chang-Long Yu; Zi-Yan Hu; Jia-Qi Chen (IEEE Access)
Bamboo furniture, as an emerging low-carbon industry, has become a significant component of the furniture sector’s sustainable development. However, unclear design elements and challenges in quantifying user needs hinder its competitiveness and product quality. To address these issues, this study employs an integrated approach combining the SECI knowledge creation model, text mining, and the AHP-QFD framework. The SECI model establishes the research process framework, while BERTopic analyzes online reviews to extract key user needs. AHP is then applied to prioritize these needs, and QFD transforms them into specific design elements and technical attributes with corresponding weights and rankings. The findings reveal that safety, comfort, and ease of use are the most critical factors, with safety identified as the core element throughout the product lifecycle. Enhancing connector performance, selecting durable materials, and optimizing ergonomic design are key strategies for improving safety and extending product lifespan. This study provides valuable insights into design elements to prioritize in bamboo furniture product development. This contributes to improved design quality and promoting sustainable growth of the industry.